Thymol, Alpha‐Tocopherol and Ascorbyl Palmitate as a Natural Feed Supplements to Modulate Immune Variables and Heterophil to Lymphocyte Ratio in Broiler Chickens - Emiliano Ariel Videla; Jorge Martin Caliva; Romina Paula Andrea Picco; Raúl Héctor Marín; Agustin Luna; Franco Nicolas Nazar (Veterinary Medicine and Science)
ABSTRACT Background Poultry housing includes unavoidable stressors that impair birds’ welfare and health. Global policies are banning antimicrobial growth promoters mainly due to antimicrobial resistance. Antioxidants modulate immunity by reducing oxidative stress, which impairs immune function. Thymol (THY), tocopherol (TOC) and ascorbyl palmitate (AP) have been studied for their antioxidant, antimicrobial and anxiety/fear‐reducing properties. However, their effects on immune function and stress responses in broilers require further investigation. Objectives This study assesses whether dietary THY or a TOC and AP mix modulates immune and chronic stress‐related responses in broilers. Methods Cobb‐500 chicks (n = 960) were assigned to one of 6 dietary treatments: (1) Basal (control), (2) Promotor (Basal + flavomycin), (3) BHT (Basal + butylated hydroxytoluene), (4) Promotor‐BHT (Basal + flavomycin + BHT), (5) THY (Basal + thymol) and (6) TOC‐AP (Basal + tocopherol + AP). Immune and stress parameters were evaluated, including inflammatory response to phytohemagglutinin‐P (PHA‐P), antibody production against sheep red blood cells (SRBC) and heterophil‐to‐lymphocyte (H/L) ratio. Results Supplementation did not affect the PHA‐P inflammatory response (p = 0.72) but influenced SRBC antibody production and H/L ratio (p < 0.003). Broilers supplemented with THY or TOC‐AP exhibited significantly lower antibody responses, potentially avoiding an energy‐demanding acquired immune activation. Additionally, both groups showed significantly lower H/L ratios, suggesting that these supplements may help mitigate physiological stress induced by routine husbandry practices. Conclusion These findings provide evidence that THY and TOC‐AP may serve as natural alternative to synthetic additives for improving welfare and mitigating stress‐induced immune imbalance under commercial rearing conditions.